Study on Quenching Characteristics and Resistance Equivalent Estimation Method of Second-Generation High Temperature Superconducting Tape under Different Overcurrent - Siyuan Liang (Materials, 2019)
In this paper, through AC and DC overcurrent tests on second generation high temperature superconducting tape (2G HTS tape), we respectively summarize the typical types of quenching resistance and corresponding quenching degree, in which there are three types under AC overcurrent and two types under DC overcurrent. According to experimental results, a rule was found that, when 2G HTS tape quenches to normal state, the relationship between quenching resistance and joule heat generated from 2G HTS tape presents a fixed trend line, and the influence of liquid nitrogen can be ignored. Then, the characteristics and rules of quenching resistance found in experiments are well explained and confirmed by a detailed 3D finite element model of 2G HTS tape including electromagnetic field and thermal field. Finally, based on above works, our group proposes a new equivalent method to estimate the quenching resistance, where the results of AC and DC overcurrent experiments can be equivalent to each other within a certain range. Compared with FEM, the method has the following advantages: (i) The method is simple and easy to implement. (ii) This method combines precision and computational efficiency. (iii) With superconducting tape quenching to normal state, this method presents a good consistency with experimental results.